MARITIME SECURITY IN SOUTH EAST ASIA: INDONESIAN PERSPECTIVE - Ariadno, Melda Kamil (Indonesian Journal of International Law, 2021)
Maritime security is an important issue particularly for the archipelagic state. As the largest archipelagic state in the world, Indonesia has its own responsibility to guard its waters from any threat. Indonesian waters have been used for centuries to accelerate international trade. In addition, Indonesia needs to address its boundary problems, handling of piracy, combating Transnational Organized Crime, such as, human trafficking, drugs trafficking, and human smuggling. This article explains on Indonesian perspective of the maritime security in South East Asia.